PSVII-22 Using GPS and genomic technologies to provide a more accurate estimate of bull power in western intermountain beef systems. (30th November 2020) - Garcia, Matthew D; Chapman, Kim; Heaton, Kevin; Thacker, Eric; Rickords, Lee; Dallin, Josh; Rood, Kerry; Hadfield, Jacob; Larsen, Ryan
Abstract: The objective of this study was to utilize GPS technology and genomic parentage testing to provide a more accurate measurement of bull power in Intermountain West beef production systems. Breeding seasons in the Intermountain West are typically conducted on expansive pastures, leading to current bull:cow ratios (1:20 or 1:25) possibly being inaccurate. Traditionally, producers maintain enough bulls to satisfy established bull cow ratios, but there was not further investigation into which calves were sired from specific bulls or how many cows each bull was actually servicing. Thus, the current study fitted five bulls with GPS collars and collected hair samples for future DNA extraction prior to the 2018 breeding season. Bull movement was tracked over a 90-day breeding season on a large grazing allotment in southern Utah and northern Arizona. The GPS collars allowed for tracking total distance traveled per day, and distance traveled away from water. Upon completion of the breeding season, collars were removed and data downloaded. A total of 104 potential offspring of the collared bulls were branded, and had ear notches collected for DNA extraction and parentage analyses. Results of parentage testing revealed that actually six bulls sired calves during the 2018 breeding season. The cooperating ranch's bulls sired 30, 16, 14, 10 and 2 calves respectively. However, a neighboring operation's bull sired 32 calves in the cooperator's herd during that same season. While results from the current study are very preliminary, they do validate the importance of verifying bull power and sire identification in order to critically evaluate sire performance and increase the accuracy of selection in breeding replacements. The information presented herein may prove useful as a future selection tool to identify bulls that are high performers during the breeding season in the Intermountain West.